The minimal membrane requirements for BAX-induced pore opening upon exposure to oxidative stress - Mystek, Paweł; Singh, Vandana; Horváth, Matěj; Honzejková, Karolína; Riegerová, Petra; Evci, Hüseyin; Hof, Martin; Obšil, Tomáš; Šachl, Radek (Biophysical journal, 2024)
Perforation of the outer mitochondrial membrane triggered by BAX and facilitated by its main activator cBID is a fundamental process in cell apoptosis. Here, we employ a newly designed correlative approach based on a combination of a fluorescence cross correlation binding with a calcein permeabilization assay to understand the involvement of BAX in pore formation under oxidative stress conditions. To mimic the oxidative stress, we enriched liposomal membranes by phosphatidylcholines with truncated sn-2 acyl chains terminated by a carboxyl or aldehyde moiety. Our observations revealed that oxidative stress enhances proapoptotic conditions involving accelerated pore-opening kinetics. This enhancement is achieved through increased recruitment of BAX to the membrane and facilitation of BAX membrane insertion. Despite these effects, the fundamental mechanism of pore formation remained unchanged, suggesting an all-or-none mechanism. In line with this mechanism, we demonstrated that the minimal number of BAX molecules at the membrane necessary for pore formation remains constant regardless of BAX activation by cBID or the presence of oxidized lipids. Overall, our findings give a comprehensive picture of the molecular mechanisms underlying apoptotic pore formation and highlight the selective amplifying role of oxidized lipids in triggering formation of membrane pores.
Keywords: Humans; Oxidative Stress; Mitochondrial Membranes; oxidační stres; poréznost; liposomy; Apoptosis; Fluoresceins; Phosphatidylcholines; mitochondriální membrány; bcl-2-Associated X Protein; protein X asociovaný s bcl-2; fosfatidylcholiny; fluoresceiny; Porosity; Liposomes; apoptóza; lidé